Implementasi Job Safety Analysis (JSA) terhadap keselamatan kerja pada proyek pembangunan polder/pompa PT. XYZ - Ardani, Natalia Caliysta; Waluyo, Minto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
JSA is Job Safety Analysis or JSA is a safety management technique that focuses on identifying hazards and controlling hazards related to a series of jobs or tasks to be performed. This study is a qualitative description with an in-depth case study approach on the PT XYZ polder/pump construction project to understand in detail the JSA implementation process. This study shows that the implementation of JSA on the pump house foundation work at the PT XYZ project has succeeded in reducing potential hazards and accident risks. The results of the study indicate that JSA is effective for use in reducing work accidents such as the stages of work items to hazard analysis and what aspects will occur to the controls used to overcome this. In the construction of polders/pumps, it can be concluded that each work item in JSA can be analyzed for follow-up with engineering control, administrative control, and PPE that must be used by workers.